Effectiveness of Quadriceps Flexibility and Vmo Strengthening Using Wall Ball Squats with Specific Exercises on Dynamic Patellofemoral Pain Syndrome in Athletes: An Observatonal Approach - Divyansh Pareek; Dr. Hirendra kumar katariya PT; Dr. Jafar khan PT (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
The primary objective of the present study is to evaluate the effectiveness of quadriceps flexibility and VMO Strengthening using wall ball squats with specific exercises on dynamic patella-femoral pain syndrome in athletes. Pre and post evaluation was performed on 15 participants using the VAS (Visual Analog Scale), Kujala Questionnaire Scale. Findings suggest Wall-ball squats offer a highly stable closed-chain position that minimizes anterior shear forces, promotes symmetrical co-contraction, and allows progressive loading without inducing excessive irritability. These characteristics likely facilitated smoother functional adaptation and higher overall performance scores. By offering controlled sagittal-plane strengthening, wall-ball squats may have better addressed the demands of functional mobility. Data suggest that the application of wall ball squats with specific exercises is effective intervention for treating dynamic patella-femoral pain syndrome in athletes.